Public Response to Halal Certification: A Study of the Interaction between MUI Fatwa and LP POM MUI - Mashudi; Ilmi, Abdullah Rosikh Fil (International Journal of Islamic Business and Economics (IJIBEC), 2024)
This study aims to describe the interaction between MUI (Indonesian Ulema Council), the Fatwa Commission, and the MUI's LP POM (Assessment Institute for Food, Drugs, and Cosmetics) regarding halal products and the response from society (both producers and consumers) towards halal product certification. This type of research is field research in the form of applied research. Data collection techniques include surveys, interviews, and documentation. The sources of research data are primary data from field research and secondary data from literature research. The data analysis technique used is qualitative, consisting of descriptive explanations, eclectic analysis, content analysis, and rationalistic analysis. Data accuracy is maintained through triangulation. This research is concentrated on the LP POM MUI in four provinces on the island of Java, with samples taken from Jakarta, Bandung, Semarang, and Surabaya. The research results indicate several important points; first, the response of producers and consumers towards the halal product certification carried out by the LP POM MUI is generally low/negative. Second, the factors causing the low/negative response from producers include the lack of certainty in halal product certification laws, the tendency of producers to prioritize business aspects, and weak government oversight of raw materials and additives that fall into the non-halal category. Third, the low/negative response from the public towards halal product certification is also influenced by low purchasing power, low education and knowledge among some Indonesian Muslims about halal products, and differences in lifestyle due to the geographical location of consumers in rural and urban areas, coastal and mountainous regions.